"It's Not Something I Chose You Know": Making Sense of Pedophiles' Sexual Interest in Children and the Impact on Their Psychosexual Identity. (September 2018) - Blagden, Nicholas James; Mann, Ruth; Webster, Stephen; Lee, Rachael; Williams, Fiona
Sexual interest in children is one of the most strongly predictive of the known risk factors for sexual reconviction. It is an important aspect of risk assessment to identify the presence of such interest, and an important task for treatment providers to address such a sexual interest where it is present. It has been argued that understanding pedophiles' deviant sexual interest in children can enhance risk assessment, management, and treatment planning. This research study aims to explore the phenomenology of deviant sexual interest in children, the impact it has on pedophilic offenders' identities, and their views on the treatability of that interest. The study used semistructured interviews and repertory grids to make sense of participants' experiences. The results revealed three superordinate themes: "'living' with a deviant sexual interest, " "relational sexual self, " and "possible and feared sexual self." The analysis unpacks these themes and repertory grid analysis is used to explore a subset of participants' identities in more detail. The results reveal that there needs to be an acceptance from both client and therapist that their sexual interest in children may never go away. Through this acceptance, clients could work on enhancing sexual self-regulation, recognizing their triggers, and so managing their sexual thoughts, feelings, and behavior. Implications for treatment are also discussed.